Кристалічна структура BaPr₂Ti₃O₁₀ - Тітов, Ю.О.; Бєлявіна, Н.М.; Марків, В.Я.; Слободяник, М.С.; Краєвська, Я.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The crystal slab perovskite-like structure of compound BaPr₂Ti₃O₁₀ synthesized by the heating of co-precipitated hydroxy-carbonates has been determined by X-ray powder diffraction, and its peculiarities are analyzed.